Estimate of the cardiovascular risk in the elderly with hypertension - Naifi Hierrezuelo Rojas; Julia Tamara Álvarez Cortés; Arianna Monje Labrada (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The necessity to diminish the morbidity and mortality due to cardiovascular and cerebrovascular diseases has been the main reason to focus the problem of   hypertension control from a more comprehensive point of view.  Objective: To estimate the cardiovascular risk in the elderly with hypertension assisted in a health area.  Methods: A descriptive and cross-sectional study of 103 elderly with hypertension, belonging to the Doctor Family Office No. 23 of Ramón López Peña Teaching Polyclinic was carried out in Santiago de Cuba, from January to December, 2019.   Some sociodemographic and clinical variables were studied (age, sex, color of the skin) and (classification and control of the disease) respectively; also, the cardiovascular risk was considered according to the Cuban guide of diagnosis, evaluation and treatment of hypertension. The techniques of the descriptive statistic were used, such as absolute frequency and percentage, as well as measures of central tendency.  Results: There was a prevalence of women, fundamentally of more advanced ages, and people with black skin. The most frequent risk factors were poor feeding, physical inactivity and diabetes mellitus. The moderate cardiovascular risk prevailed in the 56.0 % of the population.   Conclusions: The studied patients showed a moderate to high risk for presenting cardiovascular events in the next years, basic element for planning and implementing preventive and control actions that, undoubtedly, will rebound in a decrease of morbidity and mortality due to cardiovascular and cerebrovascular diseases.